2012
DOI: 10.1152/jn.01111.2011
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for landing after a self-initiated fall

Abstract: Castellote JM, Queralt A, Valls-Solé J. Preparedness for landing after a self-initiated fall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Previous reports have addressed StartReact effects only with high-intensity stimuli, and have sought startle signs mainly in either proximal or distal upper limb muscles, while only few reports have explored both proximal and distal muscles simultaneously [ 19 , 39 , 47 , 62 ]. By means of simple tasks, just flexing the elbow (FLEX) or pinching a pen (PINCH), differences in the StartReact effect across intensities became apparent between proximal and distal muscles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have addressed StartReact effects only with high-intensity stimuli, and have sought startle signs mainly in either proximal or distal upper limb muscles, while only few reports have explored both proximal and distal muscles simultaneously [ 19 , 39 , 47 , 62 ]. By means of simple tasks, just flexing the elbow (FLEX) or pinching a pen (PINCH), differences in the StartReact effect across intensities became apparent between proximal and distal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…In RT paradigms it may not only elicit a startle reaction, but also accelerate the onset of the prepared task, the so-called StartReact effect [ 8 , 9 ]. Auditory stimuli comprise the modality most extensively studied in the field of startle reactions [ 10 , 11 , 12 , 13 ] and of the StartReact effect [ 8 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The auditory domain has also been used to disentangle the underlying mechanisms of accelerated voluntary motor responses ascribed either to a high-intensity stimuli alone, or to an additional StartReact effect [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent work with human subjects has shown that humans can adapt to a loss of visual input (Santello et al 2001;Liebermann and Goodman 2007;Goroso 2009, 2011;Castellote et al 2012). For example, humans can perform coordinated drop-landings immediately after removal of continuous visual feedback and experience only slight changes to EMG and kinematic patterns (Santello et al 2001;Liebermann and Goodman 2007).…”
Section: The Importance Of Sensory Feedback For Landingmentioning
confidence: 99%
“…Early analyses hypothesized that the rapid release of SAS-induced responses is the result of triggering subcortically stored information with faster neural transmissions (Carlsen et al, 2004; see also Castellote et al, 2012; Nonnekes et al, 2014). However, recent transcranial magnetic stimulation (TMS) studies show that the StartReact effect may not be limited to subcortically stored programs, but can also be observed in cortically dependent processes (Alibiglou and MacKinnon, 2012; Stevenson et al, 2014).…”
mentioning
confidence: 99%